2011
DOI: 10.1007/s00425-011-1419-7
|View full text |Cite
|
Sign up to set email alerts
|

A nodulin/glutamine synthetase-like fusion protein is implicated in the regulation of root morphogenesis and in signalling triggered by flagellin

Abstract: The nodulin/glutamine synthetase-like protein (NodGS) that we identified proteomically in Arabidopsis thaliana is a fusion protein composed of an N-terminal amidohydrolase domain that shares homology with nodulins and a C-terminal domain of prokaryotic glutamine synthetase type I. The protein is homologous to the FluG protein, a morphogenetic factor in fungi. Although genes encoding NodGS homologues are present in many plant genomes, their products have not yet been characterized. The Arabidopsis NodGS was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Glutamine synthetase is beneficial to nitrogen assimilation and has been founded in prokaryotes and eukaryotes (Doskočilová et al, 2011). Viégas and Silveira (1999) found that salinity imposed sensitivity on nitrogen assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine synthetase is beneficial to nitrogen assimilation and has been founded in prokaryotes and eukaryotes (Doskočilová et al, 2011). Viégas and Silveira (1999) found that salinity imposed sensitivity on nitrogen assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus FluG is a fusion protein composed of an N-terminal amidohydrolase domain that shares ho-mology with nodulins (Nod) and a C-terminal prokaryotic glutamine synthetase (GS) type I domain. Proteins similar to FluG are also found in plants (14,30). FluG is predicted to be capable of carrying out condensation of glutamate with an amino-groupcontaining molecule and subsequent hydrolysis; the signaling molecule had been proposed to be aminobutyrate (22).…”
Section: Discussionmentioning
confidence: 99%
“…Such an interaction may not occur in A. flavus, as suggested by the yeast two-hybrid results, because A. flavus normally conidiates in the dark. The Arabidopsis NodGS protein is part of a large heterogeneous protein complex (14). FluG-dependent conidiation in A. nidulans appears to be regulated by a suppressor, SfgA (38).…”
Section: Discussionmentioning
confidence: 99%
“…The nodulon/glutamine synthetase-like protein (NodGS) proteomically identified in Arabidopsis thaliana is a fusion protein containing a C-terminal domain of prokaryotic GSI. It does not possess glutamine synthetase activity, but plays a role in root morphogenesis and microbial elicitation (Doskocilova et al, 2011). …”
Section: Discussionmentioning
confidence: 99%